Trust in leadership and incentives: Experimental study of whistleblowing intention - Ema Yulianing Tyas; Intiyas Utami (Jurnal Akuntansi dan Auditing Indonesia, 2020)
Whistleblowing is a disclosure act made by members of organization related to illegal practices of the organization. Trust in leadership and incentive is related to whistleblowing intention and has become a consideration for a whistleblower in conducting his/her whistleblowing actions. When an employee knows the existence of fraud, he can report the fraud to the leaders of his company when he believes that the leaders of his company can eradicate that fraud. This study was accounting undergraduate students as subjects. This study was aimed to examine the potential of employees’ whistleblowing intentions in the existence of trust toward their leaders and in the existence of incentives. This study used an experimental design of 2x2 between subjects. The treatments were given in the form of trust in leadership (high and low level of leadership) and incentives (existence of incentives and no incentives).